2008
DOI: 10.1002/anie.200803793
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Palladium(II) Complexes Possessing a Tridentate N‐Heterocyclic Carbene Amidate Alkoxide Ligand: Access to Oxygen‐Bridging Dimer Structures

Abstract: N-Heterocyclic carbenes (NHCs) and their palladium complexes have been developed to facilitate the formation of carbon-carbon and carbon-heteroatom bonds.[1] NHC complexes exhibit unique chemical properties such as strong Pd-NHC s bonding, which enhances the stabilities of active organometallic compounds relative to conventional phosphane complexes.[2] Moreover, chiral NHC ligands have been synthesized to promote asymmetric catalysis. [3] Most of the chiral NHC ligands that have been utilized for asymmetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 123 publications
(67 citation statements)
references
References 37 publications
4
63
0
Order By: Relevance
“…The reaction mixture was stirred under refluxing for 15 h. After cooling the solution at room temperature, a white solid, which is the desired product, was filtrated and then washed with THF. These compounds were reported previously [10]. 6, 137.6, 123.6, 122.9, 61.0, 56.4, 50.6, 35.8, 28.2, 19.5, 18.1.…”
Section: -[2-((s)-1-hydroxy-3-methyl-2-butanylamino)-2-oxoethyl]benzsupporting
confidence: 82%
See 2 more Smart Citations
“…The reaction mixture was stirred under refluxing for 15 h. After cooling the solution at room temperature, a white solid, which is the desired product, was filtrated and then washed with THF. These compounds were reported previously [10]. 6, 137.6, 123.6, 122.9, 61.0, 56.4, 50.6, 35.8, 28.2, 19.5, 18.1.…”
Section: -[2-((s)-1-hydroxy-3-methyl-2-butanylamino)-2-oxoethyl]benzsupporting
confidence: 82%
“…The filtrate was concentrated under reduced pressure, which was purified by column chromatography on silica gel using AcOEt followed by MeOH as an eluent to afford 2 or 5 as a white solid. These compounds were reported previously [10]. (d, J = 6.6 Hz, 3H), 0.90 (d, J = 6.6 Hz, 3H); 13 C NMR: d 169.3,139.4,128.9,121.7,62.9,58.3,50.3,30.0,19.9,18.7.…”
Section: General Procedures For Preparation Of 2 Andsupporting
confidence: 79%
See 1 more Smart Citation
“…Alternatively, the presence of HOAc as the product from chelation of the carboxylate when starting with complex 5 may induce nonproductive side reactions such as hydro-dehalogenation. Attempts to improve catalysis by abstracting the chloride ligand in complex 7 with AgBF 4 only gave catalytically inactive species and no product formation was observed even after 24 h. This result may be due to the formation of a bimetallic system [27]. General reaction conditions: styrene (560 µmol), NaOAc (440 µmol), bromoanisole (400 µmol) and palladium complex (1 mol%) in DMA (3.0 mL) at 50°C, 2 h; NMR spectroscopic yield.…”
Section: Cross-coupling Catalysismentioning
confidence: 99%
“…The literature provide with information on dimeric and monomeric square planar palladium(II) derivatives of N-heterocyclic carbene amidate alkoxide having both N-Pd-O chelating stretching modes. The Xray structural analysis of these palladium compounds showed that the dimer has shortened metal oxygenbridging bond length in comparison to the oxygen-terminal bond in the monomer [19]. The structural determination of dimeric square pyramidal copper(II) compounds derivative of N-(salicylidene)-N'-(imidazol-2-ylmethylene)-1,3-propanediamine) also showed elongated metal oxygen-bridging bond length in addition to shortened ones which are associated with the axial or equatorial positon of the oxygen atoms within the structure.…”
Section: Synthesis Characterisation and Antimicrobial Activity Of DImentioning
confidence: 99%